Analisis Keterbatasan Intervensi Pemerintah Kota Jakarta Utara Pada Tahun 2023-2024 terhadap Perkawinan Anak melalui Perspektif Keadilan Lingkungan - Athaya Salsabila; Irwansyah (Pusat Studi Gender, Universitas Kristen Indonesia, 2025)
This journal article explains the government's inability to mitigate the adaptive response of coastal communities to climate change, which involves marrying off their daughters at a young age due to environmental injustice. This journal article will explain various government policies and programs regarding child marriage, such as including child marriage in the 2020- 2024 Long-Term Development Plan (RPJMN), revising the minimum age limit for marriage, the National Strategy for Preventing Child Marriage, and the Women and Children Friendly Village Program. However, the number of child marriages has decreased at a slow rate in the last decade. Thus, this study aims to answer why government intervention programs have not been able to overcome the phenomenon of child marriage triggered by climate change in Cilincing, North Jakarta. This study will examine it through four factors of Environmental Justice by Scholsberg (2007), namely recognition, participation, capability, and fair distribution. This study was conducted using qualitative approach through primary and secondary data. Primary data were obtained from the interview process with the North Jakarta Women's Empowerment, Child Protection and Population Control Department, KIARA, Rumah KitaB and the Cilincing community. Meanwhile, secondary data were obtained from previous research, journal articles, and other sources. Based on the results of data collection, this study found that environmental and political injustice of Cilincing women was caused by the government failure to fulfill the factors of recognition, participation, capability, and fair distribution towards the Cilincing community in designing development programs and projects that were planned not based on the interests of the community